Experimental investigation on interaction of vortex finder diameter and length in a small hydrocyclone for solid-liquid separation. Issue 5 (24th March 2022) - Liu, Hongyan; Yin, Qing; Huang, Qingshan; Geng, Shujun; He, Taobo; Chen, Aqiang
ABSTRACT: Influences of the vortex finder diameter and length on the performance of a 50 mm diameter hydrocyclone for particle separation were investigated comprehensively, and the grade efficiencies of particles as well as the cut-size were analyzed detailedly. The results indicated that the separation efficiency could be promoted by employing a vortex finder with a small diameter and appropriate length, and the optimum length highly depends on the vortex finder diameter. It is observed that the optimum length of the vortex finder increases first and then decreases with the increase of its diameter. Additionally, the grade efficiencies demonstrate that large particles (>25 μm) can be almost entirely separated when the vortex finder diameter is lower than 20 mm, and large particles will escape from the vortex finder if the vortex finder diameter is too large (i.e., 25 mm). Besides, the impacts of the vortex finder diameter and its length on the cut-size are negligible when a small diameter vortex finder (less than 20 mm) is employed, while the cut-size increases significantly when a large vortex finder is used. Finally, empirical correlations have been established to quantitatively predict the optimum vortex finder length, separation efficiency, and Euler number.